Sistem Bagi Hasil Peternak Sapi Ditinjau Dari Ekonomi Islam Studi Kasus Di Desa Sisik Kecamatan Praya Barat Lombok Tengah - Habibul Umam Taqiuddin; Dedi Riswandi; Ria Alfiani; Baiq Solatiyah (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2022)
The purpose of this study was to find out the system for the results of the cattle business in Sisik Village and the distribution of the proceeds from the sale of livestock carried out by shahibul maal and mudharib according to the agreement. The method used is a qualitative method with primary and secondary data collection techniques. Based on the results of the study, it can be concluded that the profit sharing system for cattle farming in Sisik Village after being reviewed using an oral contract in its implementation, 100% capital is given to mudharib and the agreed profit sharing is 50%: 50% profit value is in accordance with the portion and responsibility answer. And the division of the calf system is by giving the first benefit to mudharib and the second to shahibul maal.